2021
DOI: 10.3390/f12070850
|View full text |Cite
|
Sign up to set email alerts
|

Compost and PGP-Based Biostimulant as Alternative to Peat and NPK Fertilization in Chestnut (Castanea Sativa Mill.) Nursery Production

Abstract: In forest nurseries, intensive use of non-renewable substrates such as peat and high application rates of chemical synthesis fertilizers lead to environmental problems and high susceptibility to biotic and abiotic stresses. This work aims to seek more sustainable crop management to help mitigate these problems, combining the substitution of peat by compost and the use of growth-promoting microorganisms (PGPs) as a fertilization tool. For this purpose, a trial was carried out to test the effectiveness of an agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
2
3
0
1
Order By: Relevance
“…The initial electrical conductivity (EC) in all compost-based substrates values ranged between 4.27 (40CA) and 18.05 dS m −1 (80CHA), which was significantly higher than that of the control (1.32 dS m −1 ) (Table 3). It could also be observed that the EC was affected by the percentage of compost, increasing with the ratio of compost in the substrate, which is in line with previous results [17,24,32]. In addition, the EC changed depending on the type of compost incorporated into the potting media, with higher values in the CHA treatment, followed by CPA and CA.…”
Section: Effects Of Treatments On the Initial And Final Chemical Prop...supporting
confidence: 90%
See 3 more Smart Citations
“…The initial electrical conductivity (EC) in all compost-based substrates values ranged between 4.27 (40CA) and 18.05 dS m −1 (80CHA), which was significantly higher than that of the control (1.32 dS m −1 ) (Table 3). It could also be observed that the EC was affected by the percentage of compost, increasing with the ratio of compost in the substrate, which is in line with previous results [17,24,32]. In addition, the EC changed depending on the type of compost incorporated into the potting media, with higher values in the CHA treatment, followed by CPA and CA.…”
Section: Effects Of Treatments On the Initial And Final Chemical Prop...supporting
confidence: 90%
“…The control treatment resulted in the lowest pH, followed by 40CA. As previously reported [16,17], the pH increased with an increase in the ratio of compost, with the 80CHA and 80CPA treatments having the highest values.…”
Section: Effects Of Treatments On the Initial And Final Chemical Prop...supporting
confidence: 85%
See 2 more Smart Citations
“…Struktur kolonisasi yang terbentuk pada pengamatan 6 MSI ialah hifa eksternal, apresorium, hifa internal, dan struktur menyerupai klamidospora (Gambar 4). Cendawan mutualistik akar mengkolonisasi secara internal akar tanaman dan mengeksplorasi lingkungan rizosfer untuk mengeksplorasi sumber karbon, berkompetisi untuk ruang, air, dan nutrisi sehingga dapat meningkatkan kapasitas kompetitif dan menguntungkan tanaman inang (Fuertes-Mendizábal et al 2021).…”
Section: Respons Tumbuh Tanaman Inangunclassified